Implementation of Expert System in Diagnosing Torch Disease Using The Certainty Factor Method - Nusa Ichdia Hady Perdana; Reno Tanfidz; Stevila; Siti Aisyah (Jurnal Mantik, 2021)
The development of science and technology is currently very fast in line with the increasingly high human needs. Technology that develops in accordance with the demands of the times is a very supportive means of dealing with various problems that exist in hospitals, agencies and other organizations. TORCH disease is not a disease that cannot be cured but must be watched out for especially in pregnant women because of the consequences that can occur to the fetus such as physical disabilities, mental disabilities or spontaneous abortion. TORCH stands for Toxoplasma, Rubella, Cytomegalovirus and Herpes II. Expert system application to determine the TORCH virus using the certainty factor method.